The dose of febuxostat required to achieve the target level of uric acid in patients with normal and impaired renal function - M. S. Eliseev; M. N. Chikina; O. V. Zhelyabina; Ya. I. Kuzmina (Современная ревматология, 2025)
Febuxostat (FS) is the drug of choice in impaired renal function, but the dosage regimen and the actual efficacy of the maximum allowable doses required to achieve the target uric acid (UA) level in patients with impaired renal function have not been adequately studied.Objective: to compare the dosage of FS required to achieve the target level of UA in blood serum in patients with gout with normal or near normal (glomerular filtration rate (GFR) >60 ml/min/1.73 m2) and moderately impaired (GFR 30–60 ml/min/1.73 m2) renal function.Material and methods. The study included 159 patients with gout who were not receiving urate-lowering medication and had serum UA levels above 360 μmol/l. The patients were divided into two groups: with GFR >60 ml/min/1.73 m2 (n=123) and GFR 30–60 ml/min/1.73 m2 (n=36). All patients were prescribed FS at a dose of 80 mg/day. If the target serum level of UA was not reached, the dose of the drug was increased to 120 mg/day. The observation period was at least 6 months (26 weeks).Before the start and after the end of the observation period, complete blood count (CBC), serum levels of glucose, creatinine, UA, transaminases and creatine phosphokinase were assessed. GFR was calculated according to CKD-EPI formula. In two groups of patients, changes in UA serum levels, the probability of reaching the target UA level in the blood (<360 μmol/l) against the background of FS therapy and the dose of the drug required for this were analyzed.Results and discussion. Data from 152 patients who completed the study were analyzed: 34 of 36 patients with GFR 30–60 ml/min/1.73 m2 and 118 of 123 with GFR >60 ml/min/1.73 m2. During the observation period, 129 (84.9%) of 152 patients reached the target level of serum UA: 101 (85.6%) of 118 patients with GFR >60 ml/min/1.73 m2 and 28 (82.4%) of 34 with GFR 30–60 ml/min/1.73 m2 (p=0.6). In the GFR >60 ml/min/1.73 m2 group in 68 (67.3%) patients FS dose of 80 mg/day was enough to achieve the target level of UA and in 33 (32.7%) the dose of 120 mg/day was requires, and for the GFR 30–60 ml/min/1.73 m2 group such doses were required in 13 (46.4%) and 15 (53.6%) patients, respectively (p=0.04). The dose of the prescribed drug after the adjustment until the target level of UA was reached was statistically lower in patients with GFR >60 ml/min/1.73 m2 (93.1±18.9 mg/day) than in the group of patients with GFR 30–60 ml/min/1.73 m2 (101.4±20.3 mg/day), p=0.04.Conclusion. The efficacy of FS does not decline in patients with gout and moderate decline in renal function. In more than 80% of cases it is possible to achieve the target level of UA in these patients, but it is associated with the need to use the maximum daily doses of the drug.